Kekuatan Sambungan Miring (scraf joint) Kayu Sengon Pada Struktur Balok Kayu Laminasi (glugam beams) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Nowadays, the needs of woods for structure is difficult to obtain, especially for woods which has large in size and good in quality. This condition happens due to the decrease of supply from natural forest. To anticipate this circumstance, it is necessary to find an alternative composite wood using fast grow woods with low quality characteristics. The technique can be used for this is laminating technique. This research aims to investigate the strength of butt joint in glulam beams made from Sengon (Paraserianthes falcataria) wood and laminated using Urea Formaldehyde adhesive. The specimen of glulam beam has size of 75 mm in width, 145 mm in thickness, and 2500 mm in length, with three various slope of scarf joint, which arel/h = 3